2016
DOI: 10.1111/ped.12892
|View full text |Cite
|
Sign up to set email alerts
|

Chronic active EBV infection with features of granulomatosis with polyangiitis

Abstract: Herein, we report the case of a 13-year-old boy with multiple recurrent ulcers on his legs. He developed severe sinusitis at 10 years of age and had significant weight loss (6 kg) in the 2 months prior to admission. Histology of tissue biopsied from the ulcer indicated small vessel vasculitis and granulomatous inflammation. Given that these findings met the diagnostic criteria for granulomatosis with polyangiitis (GPA), he was treated with immunosuppressive agents. Further pathology, however, indicated Epstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These findings suggest that testing for EBV needs to be considered for the accurate diagnosis and classification of CNS vasculitis. Only one study has reported a case of chronic active EBV infection with the features of granulomatosis with polyangiitis because it is very rare . Other studies have described encephalitis due to EBV with HIV infection; on the other hand, our case was HIV‐negative, and thus, EBV may have played a more significant role in the development of vasculitis.…”
Section: Discussionmentioning
confidence: 68%
“…These findings suggest that testing for EBV needs to be considered for the accurate diagnosis and classification of CNS vasculitis. Only one study has reported a case of chronic active EBV infection with the features of granulomatosis with polyangiitis because it is very rare . Other studies have described encephalitis due to EBV with HIV infection; on the other hand, our case was HIV‐negative, and thus, EBV may have played a more significant role in the development of vasculitis.…”
Section: Discussionmentioning
confidence: 68%
“…Sixty to seventy percent of the patients are carrier of this organism in their nasal canals. Apart from S. aureus, other organisms are: Streptococcus pneumoniae, Haemophilus influenzae, Klebsiella pneumoniae, hepatitis C virus (HCV), Epstein-Barr virus (EBV) and Helicobacter pylori [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%